IN VITRO SCREENING OF GROUNDNUT (ARACHIS HYPOGAEA L.) VARIETIES FOR DROUGHT TOLERANCE USING POLYETHYLENE GLYCOL (PEG 6000) - Abdulmalik, M. M.; Usman, I. S.; Usman, A.; Mohammed, M. S.; Sani, L. S. (FUDMA Journal of Sciences, 2023)
Drought has been a major environmental factor contributing to reduced crop productivity. Identifying groundnut varieties that are drought tolerant will be of immense importance to the improvement of the crop. The study aimed at screening groundnut varieties for drought tolerance under in vitro condition using polyethylene glycol (PEG 6000). Treatments comprise of six varieties of groundnut (SAMNUT 14, SAMNUT 22, SAMNUT 23, SAMNUT 24, SAMNUT 25 and SAMNUT 26) and different concentration of PEG 6000 (0, 20, 40, 60g/L). The treatments were laid out in a Completely Randomized Design with three replications. Embryonic axes explants were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of PEG for shoot formation. Data were collected on shoot lengths, number of leaves per plantlet, number of roots and root length. A significant (P<0.05) reduction was observed in all the treatments as the concentration of PEG increases. Significant (P<0.05) variation was also observed among the varieties in response to the PEG treatment. The highest number of roots was observed in SAMNUT 24 (8.9), SAMNUT 25 (8.8), and SAMNUT 26 (7.5). These varieties also recorded the root lengths of 3.1cm, 3.7cm and 2.5cm respectively, which were the highest, suggesting these varieties to be drought tolerant. The results indicated that PEG (6000) can be used for simulating water stress under in vitro condition. This study will serve as a baseline for future in vitro screening for drought tolerance in groundnut.